Madura Scraptrade: Marketplace Besi Tua Berbasis Web - Antoni, Fakhri; Zaeni Lafarup, Muhamad; Muhammad Maulana Pamungkas, Nur; Al Islami, Hidayatullah (CV. Shofanah Media Berkah, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the scrap metal sector often face significant operational management challenges due to reliance on manual record-keeping methods. This process is prone to data input errors and causes delays in transaction summaries and financial reporting. This study aims to develop and implement a web-based information system to digitize business processes at Besi Tua Madura, an MSME in this sector. The system was developed using the Modified Waterfall methodology through stages of requirements analysis, design, implementation, and testing. Technologies used include PHP, MySQL, and Bootstrap to ensure responsive interface and functionality. Functional testing was conducted using the black-box method to verify the suitability of implemented features with defined user needs. The results indicate that the system successfully manages item data, records sales and purchases, generates stock reports, and provides financial visualization. The system implementation significantly aids in faster decision-making and improves overall operational efficiency.